DEMAND MANAGEMENT IN MODERN ELECTRIC POWER SYSTEMS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
In recent years, due to the energy transition taking place in many countries around the world, processes of energy transition have also begun in Uzbekistan. This transition is associated with a shift toward green energy and the solution of the problem of diversifying energy sources, the development of market relations, as well as the digitalization and intellectualization of the energy sector. Under these conditions, at all stages of the transition, it is necessary to ensure the reliability of electricity supply to consumers and the stable operation of electric power systems (EPS) under various operating modes. Therefore, conducting research on the use of effective methods to reliably supply consumers with high-quality electric energy, including during the operation of wind and solar power plants with unstable operating modes, is highly relevant. One of such effective methods is operational demand management.